The Efficacy of Employee Wellness Programs in Achieving Job Satisfaction - Shinta Ath Thariq Apriari (Managing: Jurnal Bisnis dan Manajemen, 2025)
Until now, increasingly complex and diverse work demands have positioned employee welfare as a critical issue in the industrial world. In line with the regulation of Permenaker Number 5 of 2018 and BUMN Circular Letter Number 1 of 2024, mental health is one of the important aspects that must be considered by companies. Ideally, the Employee Wellness Program (EWP) is one way to overcome problems that interfere with employee productivity, but many companies do not implement EWP as a preventive and curative measure. This is motivated by the perception that EWP is not an urgent matter for a number of companies. Therefore, this study wants to explore the various efficacy factors in achieving job satisfaction through EWP and the relationship between EWP and employee job satisfaction. This research is a type of literature study that analyzes relevant literature with the help of a search using Publish of Perish. The results of this study are that the success factor of EWP requires company awareness regarding the role of EWP as humanizing employees through ensuring physical and mental health and work-life balance so as to improve the quality of performance, loyalty and job satisfaction of employees.